The Impact of Engagement Model Academic Advising on Involvement, Academic Self-Efficacy, and Perceived Cohesion of Online Adult Learners - Jeremy Schwehm; Elizabeth Giroir (Adult Education Research Conference, 2013)
In this paper, the researchers present an ongoing study to better understand the faculty advisor role in guiding adult learners in online programs to degree completion. The researchers present a brief review of relevant literature, a research design, initial data analysis, and additional research questions that emerged from the data.